حقوق نسواں:اسلامی تعلیمات اورمعاصر نسوانی تحریکوں کے رویوں کا تقابلی مطالعہ : Women’s Rights: A Comparative Study of Islamic Teachings and Attitudes of Contemporary Feminist Movements - Abdul Rahman; Dr. Jamil Akhtar (Al-Qamar, 2020)
This article examines the attitudes and slogans of feminist movements in the light of Islamic teachings on women’s rights and seeks to clarify the difference between their attitudes and Islamic teachings. In this regard various Islamic teachings regarding women have been presented and compared with the claims and attitudes of such movements. The study finds that Islam not only mentioned the rights of women but also gave a high status to women in the society. Islam mandates respect and dignity to women. It maintains that Islam has given women very balanced rights, which modern feminist movements, despite all their claims, have failed to provide.